2008
DOI: 10.1021/ja710536p
|View full text |Cite
|
Sign up to set email alerts
|

A Nanocarbon Film Electrode as a Platform for Exploring DNA Methylation

Abstract: We describe the quantitative nonlabel electrochemical detection of both cytosine (C) and methylcytosine (mC) in oligonucleotides using newly developed nanocarbon film electrodes. The film consists of nanocrystalline sp2 and sp3 mixed bonds formed by employing the electron cyclotron resonance (ECR) sputtering method. We successfully used this film to develop a simple electrochemical DNA methylation analysis technique based on the measurement of the differences between the oxidation currents of C and mC since ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 20 publications
3
131
0
Order By: Relevance
“…However, conventional electrodes including glass-carbon or graphite cannot detect kynurenic acid, since the materials of these conventional electrode become unstable upon the application of high oxidation potential (Niwa et al, 2006). In contrast, the quantification limit of our NCE-HPLC method for kynurenic acids was 2 fmol·10 mL -1 (0.2 nM) because the NCE exhibited excellent electrochemical performance including stability and low background noise level at the oxidation potential region of kynurenic acid compared with other conventional glass-carbon or graphite electrodes for HPLC (Niwa et al, 2006;Kato et al, 2008). Furthermore, the NCE-HPLC also demonstrated that TeNT and FLC, but not TTX, markedly decreased the basal and K + -evoked releases of kynurenic acid in the mPFC.…”
Section: Figurementioning
confidence: 91%
“…However, conventional electrodes including glass-carbon or graphite cannot detect kynurenic acid, since the materials of these conventional electrode become unstable upon the application of high oxidation potential (Niwa et al, 2006). In contrast, the quantification limit of our NCE-HPLC method for kynurenic acids was 2 fmol·10 mL -1 (0.2 nM) because the NCE exhibited excellent electrochemical performance including stability and low background noise level at the oxidation potential region of kynurenic acid compared with other conventional glass-carbon or graphite electrodes for HPLC (Niwa et al, 2006;Kato et al, 2008). Furthermore, the NCE-HPLC also demonstrated that TeNT and FLC, but not TTX, markedly decreased the basal and K + -evoked releases of kynurenic acid in the mPFC.…”
Section: Figurementioning
confidence: 91%
“…In terms of DNA electroanalysis, many concepts have been reported including a hybridization-based technique with electroactive tags or intercalators, [13][14][15][29][30][31][32][33][34][35][36][37] and the direct oxidation of DNA. [38][39][40][41][42][43][44][45][46] More recently, a nanopore-based DNA analysis approach has generated much interest for the high throughput sensing of individual nucleic acids. [47][48][49][50][51][52][53][54] This paper summarizes these techniques as shown in Fig.…”
Section: Dna Electroanalysismentioning
confidence: 99%
“…Palec ek reported a DNA detection approach based on electrochemical reduction at a mercury electrode, 38 since then, some groups have already reported that the electrochemical oxidation and reduction of DNA bases can be observed at some electrodes including Au and carbon-based electrodes. [40][41][42][43][44][45][46][66][67][68][69][70] In particular, the direct oxidation of guanine at certain electrodes has often been investigated since guanine exhibits the lowest oxidation potential of all the DNA bases. [40][41][42][43][44][45][46] Moreover, ruthenium or osmium complexes can be used to mediate the oxidation of guanine (indirect electrochemistry).…”
Section: ·2 Oxidation Of Dna Basesmentioning
confidence: 99%
“…We have already reported the surface and electrochemical properties of these films, [15][16][17][18][19] and their various advantages as regards SECM measurements based on our concept, namely a homogeneous structure over the entire region, sufficient conductivity for electrochemical measurements (>20 S/cm) and an angstrom-level flat surface. 15,16 A photoresist TSMR-C90LB (Tokyo Ohka Kogyo Co., Ltd., Kawasaki, Japan) was spin-coated on the ECR nano-carbon substrate.…”
Section: Patterning Of Oxygen Functionalities On Carbon Electrodementioning
confidence: 99%